Classification and phylogenetic relationship of microaerophilic actinomycetes - PINE, LEO (International Journal of Systematic and Evolutionary Microbiology, 1970)
ABSTRACT In consideration of the genera proposed for the family Actinomycetaceae, weighted considerations were given to the factors of morphology, carbon dioxide and oxygen utilization, anaerobic and aerobic fermentation balances, glucose metabolism, presence of catalase and haemoproteins, and cell wall composition. Primarily, on the basis of cell wall composition but strongly supported by metabolic and fermentation characteristics, it was concluded the genus Arachnia belongs in the family Propionibacteriaceae. Similarly, the genus Bacterionema is more suitable within the family Mycobacteriaceae or Corynebacteriaceae. The family Actinomycetaceae would retain Actinomyces israelii, A. bovis, A. naeslundii, A. odontolyticus, A. viscosus, and Rothia dentocariosa.